Influence of Environmental Factors on the Presence and Severity of Molar Incisor Hypomineralization - Fernanda Mafei Felix da Silva; Fernanda Gabriela de Fatima Vieira; Thais Rodrigues Campos Soares; Flavia Martinez de Carvalho; Alexandre Rezende Vieira; Marcelo de Castro Costa (Association of Support to Oral Health Research (APESB), 2021)
Objective: To assess the association between environmental factors during pregnancy and early childhood with the presence and severity of Molar Incisor Hipomineralization (MIH). Material and Methods: This cross-sectional study was conducted with 120 patients between 7 and 14 years of age. MIH was evaluated according to EAPD criteria. Data collected included the child's medical history and the mother's health. Chi-square and logistic regression were performed to determine any statistical evidence of the environmental factors, with the significance level set at 5%. Results: The participants were divided into groups with MIH (n=60) and without MIH (n=60), with average ages of 9.9 (±1.9) and 9.7 (±1.7) years, respectively. There was a statistically significant difference between intercurrences during pregnancy (OR=3.55; IC95%=1.35-10.57) and medication taken by the child (OR=3.01; IC95%=1.74-8.42) and the presence of MIH. In addition, other variables were also associated with the MIH (p≤0.05). However, there was no association with variables and degree of MIH severity (p>0.05). Conclusion: The use of medications in childhood and complications during pregnancy can be association to the presence of MIH. However, these factors do not interaction to MIH severity.